Perubahan Paradigma Kepemimpinan Sekolah - Thamara Safitri; Masduki Asbari; Ahlul Bae'atun Nisa; Fitri Fatmawati (AGUSPATI RESEARCH INSTITUTA, 2023)
The purpose of writing this article is about school leadership 2.0. It explains how the thinking of a leader can change at any time including in this new era. The changes that occur cannot be separated from the rapid development of technology in all fields. The writing of this article uses a descriptive qualitative method by doing simak catat because the source of data obtained by listening to oral narratives from the Youtube channel KEMENDIKBUD RI entitled